2020
DOI: 10.1038/s41598-020-72792-z
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific strategies of 2′-fucosyllactose, 3-fucosyllactose, and difucosyllactose assimilation by Bifidobacterium longum subsp. infantis Bi-26 and ATCC 15697

Abstract: Human milk provides essential nutrients for infant nutrition. A large proportion of human milk is composed of human milk oligosaccharides (HMOs), which are resistant to digestion by the infant. Instead, HMOs act as a bioactive and prebiotic enriching HMO-utilizing bacteria and cause systematic changes in the host. Several species of Bifidobacterium have been shown to utilize HMOs by conserved, as well as species-specific pathways, but less work has been done to study variation within species or sub-species. B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 85 publications
6
49
0
Order By: Relevance
“…suis and B. longum subsp. longum strains [68] , [159] , [160] , [161] , [162] , [163] , [164] , [165] , [166] , [167] . Not by chance, in silico investigations have revealed conserved gene clusters encoding ABC transporters with high affinity binding proteins, upstream regulatory elements and one or multiple GHs that, as a whole, represent the genetic arsenal through which the abovementioned bifidobacterial species degrade and internalize HMOs [9] , [11] .…”
Section: Extracellular Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…suis and B. longum subsp. longum strains [68] , [159] , [160] , [161] , [162] , [163] , [164] , [165] , [166] , [167] . Not by chance, in silico investigations have revealed conserved gene clusters encoding ABC transporters with high affinity binding proteins, upstream regulatory elements and one or multiple GHs that, as a whole, represent the genetic arsenal through which the abovementioned bifidobacterial species degrade and internalize HMOs [9] , [11] .…”
Section: Extracellular Polysaccharidesmentioning
confidence: 99%
“…Specifically, the B. longum subsp. infantis genome possesses a contiguous genomic segment encoding GHs active on the four HMO glycosidic linkages, represented by α-fucosidase, α-sialidase, β-galactosidase and β- N -hexosaminidase activities, and flanked by a cluster specifying an ABC transporter system composed of extracellular solute binding proteins and permeases, presumed to be required for HMO internalization [9] , [162] , [168] , [169] , [170] . However, due to the lack of identifiable secretion signals in the glycosidases produced by B. longum subsp.…”
Section: Extracellular Polysaccharidesmentioning
confidence: 99%
“…Recently, comparative genome analysis involving two strains of B. longum subsp. infantis (i.e., ATCC15697 and Bi-26) revealed that the metabolic enzymes involved in HMOs utilization appear to be conserved in this bifidobacterial taxon [ 85 ]. This comparative analysis was confirmed by metabolite analysis as well as transcriptomics assays suggesting that B. longum subsp.…”
Section: Bifidobacteria and Their Genetic Adaptation To The Human mentioning
confidence: 99%
“…infantis ATCC15697 is able to consume various HMOs simultaneously, whereas B. longum subsp. infantis Bi-26 is adapted to internalize relatively short and predominantly fucosylated HMOs [ 85 ]. In conclusion, these findings show that even though HMOs consumption is characteristic of B. longum subsp.…”
Section: Bifidobacteria and Their Genetic Adaptation To The Human mentioning
confidence: 99%
“…On the other hand, there are several FMHGs investigated, and contrary to FHMOs, appear at lower concentration but showing a higher number of different forms including lactoferrin (17%), immunoglobulins IgG (<1%), IgM (<1%), and secretory IgA (11%) [9,10,11]. Both FHMOs and FHMGs stand out for their ability to stimulate the growth of bifidobacteria [7,12], whose metabolism transforms fucosylated oligosaccharides into short-chain fatty acids (SCFAs) such as acetate, formate, lactate, pyruvate [13], which in turn stimulate the immune system by inducing the differentiation of T-regulatory cells via inhibition of histone deacetylase [14].…”
Section: Introductionmentioning
confidence: 99%